Subjective growth models in long-term forecasting of development technologies - Paradowska, Konstancja (Subiektywne modele tendencji rozwojowej w prognozowaniu rozwoju nowych technologii, 2011)
The article concerns the application issues of forecasting on the basis of subjective growth models, known from Polish literature as formal second type models. The function’s form and the parameters of such models are determined on the grounds of expert opinions, the forecasts are constructed by means of extrapolation of the model. Expert opinions, collected for the need of foresight research, allowed for the construction of prognostic subjective growth models. On their basis the ‘initial’ forecasts for the development of energetic technologies were determined; there was a proper combination of these forecasts as well as an attempt to estimate their uncertainty.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 196, s. 147-157
Keywords: nowe technologie; prognozowanie; high-tech; forecasting